Keystone protist suppression triggers mesopredator release and biotic homogenization in complex soil microbial communities - Maillard, François; Klinghammer, Fredrik; Beatty, Briana H.; Zou, Hanbang; Lara, Enrique; Hammer, Edith C. ; 0000-0003-0892-2897; Tunlid, Anders; Kennedy, Peter G. (ISME Journal, 2025)
The keystone species concept holds that certain members of an ecological community, despite their low abundance, exert disproportionately large effects on species diversity and composition. In microbial ecology, experimental validation of this concept has been limited because targeted removal of individual species remains technically challenging. Here, we developed a procedure to test the keystone species concept within a soil microbial food web by selectively suppressing a protist predator at the microscale via ultraviolet-induced phototoxicity in a microfluidic soil chip system. We targeted a hypotrich ciliate (subclass Hypotrichia), and combined microscopy with high-throughput amplicon sequencing of microbial taxonomic markers to assess, across multiple trophic levels, how its suppression affected microbial community abundance, diversity, and composition. Over the 20-day incubation, the chip system supported complex communities of bacteria, fungi, and protists. Following Hypotrichia suppression, two distinct ecological responses were observed: first, an increase in the relative abundance of flagellates, consistent with mesopredator release, accompanied by a significant rise in overall protist diversity; second, a convergence in protist community composition, indicative of biotic homogenization. Bacterial community abundance, richness, and composition remained unchanged, likely due to compensatory predation from a relative increase in bacterivorous flagellates. In contrast, fungal diversity decreased, presumably because the altered protist community favored facultative fungal consumers. Collectively, these findings provide direct experimental evidence that low-abundance microbial predators can function as keystone species, modulating predator community composition and diversity, and exerting cascading effects on lower trophic levels within microbial brown food webs.
Publisher Copyright: © The Author(s) 2025. Published by Oxford University Press on behalf of the International Society for Microbial Ecology.
Keywords: bacteria; biotic homogenization; brown food web; fungi; keystone species; mesopredator release; microfluidics; protists; trophic cascade